COULD WATER CO-MANAGEMENT CONTRIBUTE TO PEACE, IN MIDDLE EAST? - Christaras, B. (Bulletin of the Geological Society of Greece, 2010)
Water is the most precious resource in the Middle East, more important even than oil, given that while the citizens represent the 5% of the total world population, the Middle East & North Africa (MENA) region contains only 0.9% of global water resources (World Bank, 1996, Allan, 1999). For this reason, almost all conflicts, in Middle East, are mainly related to shared-water resources. Historically, water was very often used as military tool or for religious purposes, Conflicts, for water management, were known from ancient years, till to the recent time. But also in our days, by 2010, the water deficit (difference between water supply and demand) is estimated to be at around 1 billion cubic meters, explaining the importance of the water to the joint futures of Palestinians, Jordanians, and Israelis. For managing the water demand, various projects were proposed or already performed related to deep aquifers pumping, brackish-groundwater reverse-osmosis desalination, sea water desalinization, water transfer using canal or pipeline systems and dam construction. Nevertheless, it is important to understand that Peace can be possible in Middle East only if a rational and fair co-management of water resources could be real.